Pengelolaan Komunikasi Organisasi Di Dinas Pendidikan Provinsi Sumatera Utara Dalam Meningkatkan Efektifitas Kinerja Pegawai - Adam Ridwan; Fadhil Pahlevi Hidayat (Universitas Muhammadiyah Sumatera Utara, 2022)
This research is important to know the management of organizational communication in the Education Office of North Sumatra Province in increasing the effectiveness of employee performance. The type of research used in this research is qualitative research. Data collection techniques used in this study was observation, interviews, and documentation. Data analysis techniques used are data reduction, data presentation, and drawing conclusions. The results of this study are the management of organizational communication in the Education Office of North Sumatra Province, especially in the General and Personnel Fields in increasing the effectiveness of employee performance, namely communication that is carried out by vertical communication and horizontal communication. The communication is done directly and also using social media, namely whatsapp